A Danish version of the oral health impact profile-14 (OHIP-14): translation and cross-cultural adaptation - Arwa Gera; Paolo M. Cattaneo; Marie A. Cornelis (BMC, 2020)
Abstract Background The Oral Health Impact Profile-14 (OHIP-14) questionnaire assesses quality of life related to people's perception of oral disorders on their well-being. However, a translated and validated Danish version of OHIP-14 is not yet available. The purpose of this pilot study was to translate and cross-culturally adapt the English version of the OHIP-14 into Danish (OHIP-14-DK). In addition, to assess its content and face validity, internal consistency and test-retest reliability. Methods The English version of OHIP-14 was translated into Danish following a standard protocol of cross-cultural adaptation. Stages I-IV: translation phase to generate a pre-final version "OHIP-14-DK". Stage V: pre-testing phase. A random sample of 22 orthodontic patients (mean age 24.7 years, SD ±14.8; 14 females, 8 males) were selected at the Section of Orthodontics, Aarhus University, Denmark. All patients self-completed the OHIP-14-DK and were then interviewed to assess its content and face validity. Internal consistency was assessed with Cronbach's alpha coefficients. All patients completed the same questionnaire again at a one-week interval. Test-retest reliability was assessed using Spearman's correlation coefficient and intra-class correlation coefficient (ICC). Results The initial and back translations were very similar: the OHIP-14-DK proved to have a good level of equivalence with no translation errors or deviations. Furthermore, the OHIP-14-DK seemed well-adapted to Danish culture and was understood by individuals down to 12 years of age. Pre-testing demonstrated good face and content validity; interviews had a response rate of 100% and confirmed that each item was understandable without inducing reluctance or hesitation. Thus, responses were related to their corresponding item. Therefore, no final adjustments were required for the pre-tested version. Cronbach's alpha for the OHIP-14-DK subscales fell in the 0.75-0.84 range, indicating an adequate-to-good internal consistency. Spearman's correlation coefficient for the OHIP-14-DK total score was 0.77. The ICC for the OHIP-14-DK total score was 0.91. Conclusions The OHIP-14-DK seems well adapted to Danish culture, proved to be face and content valid and also showed good internal consistency and excellent reliability. However, its psychometric properties still need to be tested. Study registration Not applicable